Prospective Comparison of a Percutaneous Ventricular Assist Device and Venoarterial Extracorporeal Membrane Oxygenation for Patients With Cardiogenic Shock Following Acute Myocardial Infarction. Issue 9 (7th May 2019) - Garan, A. Reshad; Takeda, Koji; Salna, Michael; Vandenberge, John; Doshi, Darshan; Karmpaliotis, Dimitri; Kirtane, Ajay J.; Takayama, Hiroo; Kurlansky, Paul
Abstract : Background: Cardiogenic shock (CS) following acute myocardial infarction (AMI) portends a poor prognosis. Both venoarterial extracorporeal membrane oxygenation (VA‐ECMO) and a percutaneous ventricular assist device (pVAD) provide hemodynamic support for patients with CS, but little is known about the best device for this population. We sought to compare outcomes of AMI patients treated with these devices. Methods and Results: Consecutive patients with CS following AMI from April 2015 to March 2017 were enrolled prospectively if they received either device for AMI‐related CS. If patients received both devices, they were analyzed according to the first used. The primary outcome was all‐cause mortality. In total, 51 patients received VA‐ECMO or pVAD following AMI; 20 received VA‐ECMO, and 31 received pVAD. The mean age was 62.1±10.1 years, and 39 (76.5%) were men. Twenty‐four (47.1%) patients were ultimately supported by both devices simultaneously (20 pVAD‐first, 4 VA‐ECMO‐first). Patients treated with pVAD or VA‐ECMO were similar in baseline characteristics at initial device insertion except that the latter were on more vasopressors and were more likely to have an intra‐aortic balloon pump. Seventeen (33.3%) had recent cardiopulmonary resuscitation, mean lactate was 4.86±3.96 mmol/L, and mean cardiac index was 1.70±0.42 L/min per m 2 . Of the 28 (54.9%) patients surviving to discharge, 11 had received VA‐ECMO first and 17 had pVAD first ( P =0.99). Survival at 1 and 2 years did not differ significantly between device groups ( P =0.42). Conclusions: Following AMI‐related CS, pVAD‐ and VA‐ECMO‐treated patients had similar outcomes. The use of both devices simultaneously was common, with almost half of patients in persistent CS after first device deployment.